Pengaruh Pengetahuan Audit dan Komitmen Organisasi terhadap Kinerja Auditor dengan Pemahaman Good Governance sebagai Variabel Moderasi - Salwa Rahmadani; Luqman Hakim (SAFE-Network, 2026)
This study aims to examine the effect of Audit Knowledge and Organizational Commitment on Auditor Performance, with Good governance Understanding as a moderating variable in Public Accounting Firms (KAP) located in South Jakarta. The study was motivated by the importance of improving auditor performance to maintain audit quality and public trust in the public accounting profession. A quantitative research method with a survey approach was employed. Primary data were collected through questionnaires distributed to auditors working in eight Public Accounting Firms in South Jakarta. The sampling technique used was purposive sampling, resulting in 100 respondents consisting of junior auditors, senior auditors, and supervisors. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.1 software. The results indicate that Audit Knowledge has a positive and significant effect on Auditor Performance, Organizational Commitment has a positive and significant effect on Auditor Performance, and Good governance Understanding also has a positive and significant effect on Auditor Performance. The moderation analysis reveals that Good governance Understanding strengthens the relationship between Organizational Commitment and Auditor Performance. However, it does not moderate the relationship between Audit Knowledge and Auditor Performance. The findings suggest that enhancing audit knowledge, organizational commitment, and understanding of good governance principles are essential factors in improving auditor performance. Furthermore, the implementation of good governance principles can strengthen the positive influence of organizational commitment on auditor performance within Public Accounting Firms.